Implementasi Kebijakan Kampung Tangkal Corona Virus Desease-19 Di Wilayah Hukum Kepolisian Resort Musi Rawas Utara - Prihatini, Lishapsari; Mardianto, Mardianto; Sumaryanto, Eko (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
This study aims to obtain a comprehensive and comprehensive picture of the implementation of the Corona Virus Disease-19 Village Policy in the Legal Area of ​​the North Musi Rawas Police. Tangkal Village is a village where residents can work together independently to prevent the spread of Covid-19. Rantau Kadam Village, Karang Dapo District, is the first pilot village in North Musi Rawas (Muratara) Regency. This type of research is qualitative research, whose main tool is observation, and interviews are conducted in an open and unstructured manner. The findings of this study are: Implementation of the Corona Virus Disease-19 Village Policy in the Legal Area of ​​the North Musi Rawas Police Station in the Good Category. The purpose of the existence of Tangguh Village is not only to prevent the spread of the corona virus, but also to have the effect of reducing crime. Indicators and strategies for the strength of interest in the Tangkal Coronaa village program. Viral Disease-19 Musi Police in the North Rawas Legal Territory, because the village head is the ruler of the village, the main actor is the village head, where the strategy is to manipulate all sectors of society for the benefit of the village community itself.